More than solutions: Empowering students to think strategically and tactically. Issue 2 (3rd April 2017) - Del Gandio, Jason
Abstract : Courses: Communication Activism; Public Advocacy; Social Movements; Public Speaking; Persuasion; Argumentation; Public Sphere. Objectives: This semester-long activity helps students implement a solutions–strategies–tactics framework into their advocacy work. More specifically, students learn to (1) designate, research, and assess the causes of significant social/political problems; (2) design long-term strategies and chronologically arrange step-by-step tactics to address those problems; (3) devise different kinds of messages for purposes of influencing public opinion/behavior, mobilizing collective action, organizing communities into political constituencies, and swaying decision makers; and (4) develop skills and competencies for becoming agents—rather than observers—of social change.